ASSOCIATION BETWEEN SEPSIS RISK CALCULATOR AND INFECTION PARAMETERS FOR NEONATES WITH RISK OF EARLY ONSET SEPSIS - Sari, Trias Kusuma; Irwanto, Irwanto; Etika, Risa; Sampurna, Mahendra Tri Arif; Mertaniasih, Ni Made (Indonesian Journal of Tropical and Infectious Disease, 2020)
C-reactive protein (CRP) is an acute-phase reactant protein that is primarily induced by the IL-6 action during the acute phase of an inflammatory or infectious process. Bacterial infection is a potent stimulus, leading to a rapid elevation of CRP levels within hours while the CBC and symptom are often misleading and/or absent. American Academy of paediatrics (AAP) is recommended routine blood examination test Complete Blood Count (CBC), C-reactive protein (CRP), and blood culture along with empirical antibiotic in neonates with early onset sepsis risk (EOS) risk even asymptomatic. Previous study is showed there were no correlation of CRP and EOS risk. The aim of this study is to evaluate the CRP and CBC profile in neonate with risk of EOS. Methods of this study is using the sepsis risk calculator (SRC) to calculate the probability of neonatal early onset sepsis (EOS) based on maternal risk and infant’s clinical presentation. Neonates with â‰¥34 weeks of gestation who were started on antibiotic treatment after laboratory examination and blo odculture were taken. EOS risk estimation were compared including CRP, leukocyte, and thrombocyte count. ANOVA applied to distinguished laboratory examination between stratified risk groups. The result is showed using 82 subjects who met the inclusion and exclusion criterias, EOS risk level was stratified into green, yellow, and red group. The p value of CRP level, platelets, white blood cell were 0.35,0.54 and 0.48 where p value was considered as significant if < 0.5. The conclusion of this study is there were no correlation of CRP level and EOS risk ASSOCIATION BETWEEN SEPSIS RISK CALCULATOR AND INFECTION PARAMETERS FOR NEONATES WITH RISK OF EARLY ONSET SEPSIS